Ideologies underlying the use of photographs in newspaper coverage of BERSIH 3.0 rally: a social semiotic analysis - Jamali Bujang Sanawi (Universiti Kebangsaan Malaysian, 2014)
BERSIH 3.0 rally that was held on 28th April 2012 has witnessed visual war among the mass media in Malaysia which had caused polarization among the Malaysian society. This study aims to analyze how the mainstream and alternative newspapers transfuse their ideology about the rally through visual depiction of the event. Three dominant newspapers namely Utusan Malaysia, The Star and Harakah were chosen based on their political economic background and their high circulations status. Based on the visual constructions of the two mainstream newspapers; Utusan Malaysia and The Star, it is found that both newspapers were critical towards BERSIH 3.0. Apart from that, both newspapers also embedded their own racial agenda in which it was found that Utusan Malaysia tries to associate the rally with the dark tragedy of 13th May 1969 while The Star tries to neutralize the involvement of the Chinese through positive imagery. In contrast, Harakah celebrated the revival and the unity of the people from all races in their struggle towards social justice as the main theme. At the same time, Harakah visually portrayed PAS as a political party that honoured pluralism, gain acceptance from young people and committed with the PR. The research has proved that photo has the capabilities to be a medium to disseminate ideology.